Courses
Courses for Kids
Free study material
Offline Centres
More
Store

# If $\cos ecx - \cot x = \dfrac{1}{3}$, where $x \ne 0$, then the value of ${\cos ^2}x - {\sin ^2}x$ isA. $\dfrac{{16}}{{25}}$B. $\dfrac{9}{{25}}$C. $\dfrac{8}{{25}}$D. $\dfrac{7}{{25}}$

Last updated date: 20th Jun 2024
Total views: 405k
Views today: 7.05k
Verified
405k+ views
Hint: To solve this question, we will use some basic trigonometric identities and algebraic identities to evaluate the given expression. We have to remember $\cos e{c^2}x - {\cot ^2}x = 1$, also ${a^2} - {b^2} = \left( {a - b} \right)\left( {a + b} \right)$

Given that,
$\cos ecx - \cot x = \dfrac{1}{3}$ …….. (i)
We know that,
$\cos e{c^2}x - {\cot ^2}x = 1$
Using the identity, ${a^2} - {b^2} = \left( {a - b} \right)\left( {a + b} \right)$, we will expand the L.H.S,
$\Rightarrow \cos e{c^2}x - {\cot ^2}x = \left( {\cos ecx - \cot x} \right)\left( {\cos ecx + \cot x} \right)$
Put the value of $\cos ecx - \cot x = \dfrac{1}{3}$,
$\Rightarrow \cos e{c^2}x - {\cot ^2}x = \dfrac{1}{3}\left( {\cos ecx + \cot ax} \right)$
Equating this L.H.S with R.H.S, we will get
$\Rightarrow \dfrac{1}{3}\left( {\cos ecx + \cot x} \right) = 1$
$\Rightarrow \cos ecx + \cot x = 3$ ……… (ii)
Adding equation (i) and (ii), we will get
$\Rightarrow \cos ecx + \cot x + \cos ecx - \cot x = \dfrac{1}{3} + 3$
$\Rightarrow 2\cos ecx = \dfrac{{10}}{3}$
$\Rightarrow \cos ecx = \dfrac{5}{3}$
Putting this value in equation (ii), we will get
$\Rightarrow \dfrac{5}{3} + \cot x = 3$
$\Rightarrow \cot x = 3 - \dfrac{5}{3}$
$\Rightarrow \cot x = \dfrac{4}{3}$
Now, we know that
$\Rightarrow \sin x = \dfrac{1}{{\cos ecx}}$
Putting the value of cosec x, we will get
$\Rightarrow \sin x = \dfrac{1}{{\dfrac{5}{3}}}$
$\Rightarrow \sin x = \dfrac{3}{5}$
Similarly, we know that
$\Rightarrow \cot x = \dfrac{{\cos x}}{{\sin x}}$
$\Rightarrow \cos x = \cot x\sin x$
Again, putting the values of sin x and cot x, we will get
$\Rightarrow \cos x = \dfrac{4}{3} \times \dfrac{3}{5}$
Solving this, we will get
$\Rightarrow \cos x = \dfrac{4}{5}$
We have to find out the value of ${\cos ^2}x - {\sin ^2}x$
So,
Putting the values of sin x and cos x, we will get
$\Rightarrow {\left( {\dfrac{4}{5}} \right)^2} - {\left( {\dfrac{3}{5}} \right)^2}$
$\Rightarrow \dfrac{{16}}{{25}} - \dfrac{9}{{25}}$
$\Rightarrow \dfrac{7}{{25}}$
Hence, the value of ${\cos ^2}x - {\sin ^2}x$ is $\dfrac{7}{{25}}$

So, the correct answer is “Option D”.

Note: Whenever we are asked such types of questions, we have to remember the trigonometric ratios of cos x and sin x. First, we have to simplify the given expression in terms of sin x and cos x and then by solving it we will get their values. After that, we will put those values in the required expression and we will get the correct answer.